Excel as an aid to find parametric arc length in complex graph for undergraduate students - Azri, Amir Harith; Harun, Nurzalina; Sadikin, Zubaidah; Rathi, Sidik; Mohd Sidek, Nur Zafirah; Batcha, Siti Rahimah; Salim Nasir, Mohd Agos (Academica Press Solutions, 2024)
This study uses a method using excel to figure out if the graph function of Excel trendline is a liable function to aid in calculating parametric arc length for undergraduate students learning parametric equations and parametric graphs. Since there are not many software out there that are easily obtainable by students to use as a reference for them to tackle complex graph where it’s function is complicated and hard to obtain. Namely, functions that have a high power or complex combination of trigonometric functions. This method uses the Excel’s trendline function within the software to get the mathematical functions and also the graph by only using data obtain via hand drawn graph of a map route. The data then can be manipulated within excel into several segments to make out easier graph for use in calculation of parametric arc length. With this method many students and professionals that needs to find the parametric arc length of a graph can use the method as a substituted or an alternative to calculate parametric arc length using only excel. Furthermore, this method have the potential to be commercialize into being use as a way to engage students into understanding parametric concept more interactively since it can be use in real life by having them make their own graph of their surrounding and extrapolating them into using excel.